Crusading in art, thought and will
1 online resource.
Keywords: Crusade scholarship has exploded in popularity over the past two decades. This volume captures the resulting diversity of approaches, which often cross cultures and academic disciplines. The contributors to this volume offer new perspectives on topics as varied as the application of Roman law on slavery to the situation of Muslims in the Latin East, Muslim appropriation of Latin architectural spolia, the roles played by the crusade in medieval preaching, and the impact of Latin East refugees on religious geography in late medieval Cyprus. Together these essays demonstrate how pervasive the institution of crusade was in medieval Christendom, as much at home in Europe as in the Latin East, and how much impact it carried forth into the modern era. Contributors are Richard Allington, Jessalynn Bird, Adam M. Bishop, Tomasz Borowski, Yan Bourke, Sam Zeno Conedera, Charles W. Connell, Cathleen A. Fleck, Lisa Mahoney, and C. Matthew Phillips.